Addressing the cause: an analysis of suicide terrorism - Eggers, Bruce Andrew, author; Yaşar, Gamze Ҫavdar, advisor; Peek, Lori A., committee member; Daxecker, Ursula E., committee member (Colorado State University. Libraries, 2011)
Since 2001, the rate of global suicide attacks per year has been increasing at a shocking rate. The 1980s averaged 4.7 suicide attacks per year, the 1990s averaged 16 attacks per year, and from 2000-2005 the average jumped to 180 per year. What is the cause behind these suicide attacks? The literature has been dominated by psychological, social, strategic, and religious explanations. However, no one explanation has been able to obtain dominance over the others through generalizable empirical evidence. Emerging in 2005, Robert Pape put forth a theory that has risen to prominence explaining the rise of suicide attacks as a result of foreign occupation. His work and findings comprise the most controversial argument in the literature of suicide terrorism. Remaining new and untested, this study attempts to test Pape's theory of suicide terrorism by applying his theoretical framework and argument to the current suicide campaigns ongoing in Afghanistan, Chechnya, and Pakistan. Through these case studies, this research project will attempt to generalize to the greater theoretical question: What is the root cause of suicide terrorism?